Pengaruh BAP (Benzil Amino Purine) dan Ekstrak Tauge (Phaseolus aureus) terhadap Multiplikasi Tanaman Nilam (Pogostemon cablin Benth.) Secara In Vitro - Hutagaol, Aprinia; Edi, Syahmi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Patchouli (Pogostemon cablin Benth.) is a promising export commodity, so techniques such as tissue culture are needed to increase its production. This study aims to determine the effect of BAP (Benzyl Amino Purine) and bean sprout extract (Phaseolus aureus) on the multiplication of patchouli (Pogostemon cablin Benth.) in vitro. This study used a factorial Completely Randomized Design (CRD) with 4 levels of BAP concentration (0 ppm, 0.5 ppm, 1 ppm, 1.5 ppm) and 3 levels of bean sprout extract concentration (0%, 12%, 15%), each treatment was repeated 3 times. Data analysis used ANOVA and further testing with 5% DMRT test. The results showed that the administration of BAP significantly affected the increase in the number of shoots, leaves, and roots. BAP concentration of 0.5 ppm gave the best results on the growth of shoots and leaves, but the treatment without BAP actually produced the best growth in the number of roots. The combination of BAP and bean sprout extract significantly affected the number of shoots and leaves. The combination of 0.5 ppm BAP and 15% bean sprout extract produced the highest number of shoots and leaves, producing 2.92 shoots and 4.28 leaves. The interaction between BAP and bean sprout extract creates natural auxin and synthetic cytokinin hormones derived from BAP, which maintain hormonal balance to support patchouli growth.